IL-12p40 deletion aggravates lipopolysaccharide-induced cardiac dysfunction in mice - Liu, Menglin; Wang, Zhen; Zhang, Jishou; Ye, Di; Wang, Menglong; Xu, Yao; Zhao, Mengmeng; Feng, Yongqi; Lu, Xiyi; Pan, Heng; Pan, Wei; Wei, Cheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac dysfunction is one of the most common complications of sepsis and is associated with the adverse outcomes and high mortality of sepsis patients. IL-12p40, the common subunit of IL-12 and IL-23, has been shown to be involved in a variety of inflammation-related diseases, such as psoriasis and inflammatory bowel disease. However, the role of IL-12p40 in lipopolysaccharide (LPS)-induced cardiac dysfunction remains obscure. This study aimed to explore the role of IL-12p40 in LPS-induced cardiac dysfunction and its potential mechanisms. Methods In this study, mice were treated with LPS and the cardiac expression of IL-12p40 was determined. Then, IL-12p40–/– mice were used to detect the role and mechanisms of IL-12p40 in LPS-induced cardiac injury. In addition, monocytes were adoptively transferred to IL-12p40–/– mice to explore their effects on LPS-induced cardiac dysfunction. Results The results showed that cardiac IL-12p40 expression was significantly increased after treated with LPS. In addition, IL-12p40 deletion significantly aggravated LPS-induced cardiac dysfunction, evidenced by the increased serum levels of cardiomyocyte injury markers and heart injury scores, as well as by the deteriorated cardiac function. Moreover, IL-12p40 deletion increased LPS-induced monocyte accumulation and cardiac expression of inflammatory cytokines, as well as enhanced the activation of the NF-κB and MAPK pathways. Furthermore, adoptive transfer WT mouse monocytes to IL-12p40−/− mice alleviated LPS-induced cardiac dysfunction and decreased the phosphorylation of p65. Conclusion IL-12p40 deletion significantly aggravated LPS-induced cardiac injury and cardiac dysfunction in mice by regulating the NF-κB and MAPK signaling pathways, and this process was related to monocytes. Therefore, IL-12p40 show a protective role in SIC, and IL-12p40 deficiency or anti-IL-12p40 monoclonal antibodies may be detrimental to patients with SIC.